Peningkatan Pemahaman dan Praktik Cuci Tangan Remaja melalui Edukasi PHBS sebagai Pencegahan Penyakit Menular - Imelda Avia; Zuriati Zuriati; Melti Suriya; Mei Putri Crismayanti; Yanita Trisetiyaningsih; Sisca Pri Andini (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescents are a group that is highly vulnerable to the risk of infectious diseases, and this elevated risk may contribute to an increased prevalence of infections in this age group. Consistent understanding and practice of proper handwashing have been shown to reduce transmission rates of communicable diseases. Method: This activity was carried out through health education and handwashing practice using a participatory educational approach. Comprehension was evaluated using oral questions, while handwashing practice was assessed through observation of the completeness of each step. A total of 31 adolescent participants aged 16–18 years were selected using purposive sampling. The evaluation showed that understanding of Clean and Healthy Living Behavior (CHLB/PHBS) and handwashing was in the good category for 93.54% of participants and in the fair category for 6.64%, with no participants in the poor category. Handwashing practice for all participants (100%) was categorized as good, as they were able to perform the handwashing steps correctly as taught. These findings indicate that brief education combining material explanation, demonstrations, and hands-on practice is effective in improving adolescents’ knowledge and skills related to handwashing. Similar programs are recommended to be implemented regularly and integrated into school activities so that handwashing behavior becomes a sustainable habit and supports the prevention of infectious diseases among adolescents.